The Cemetery and the Fear of the Dead - Vito Carrassi (Journal of Folklore and Popular Culture, 2023)
Fear is a characteristic feature of many legends. And the fear of the death is probably our deepest fear. Death is a crucial event in folk culture, as it triggers an existential crisis which must be duly managed. The living need to distance themselves from the dead in order not to lose their own “presence” in the world. To maintain this distance, people can rely on a dedicated place, the cemetery, where the fear of the dead can be mastered and framed in a sacred dimension. Cemetery may be regarded as a liminal, hybrid space, connecting life and death, the human and the divine, the visible and the invisible. Hence, it can turn into a critical, dangerous place, a “legend landscape”, where odd, mysterious, frightening encounters are possible or, at least, believable. This is especially so if one enters a cemetery at night, when it is forbidden to the living and the darkness creates the perfect stage for fearsome presences. In the ATU 1676B narrative type, an individual bets to enter a cemetery at night in order to show her/his courage and/or refute the belief of the dead as ghosts, but this gamble results in a death from fright. A different case concerns the fate of those who face the night in the cemetery with genuine courage and respect towards the dead, as in a folktale collected by W.B. Yeats (ATU 326), and a (true) story of a woman sleeping in the cemetery (Motif Index C735.2.5). Overall, the cemetery emerges as an ideal setting for a cautionary tale, through which local communities meditate on key issues such as death, fear and belief/non-belief.